The Nobel Roll of Honor: Comparing literatures and compiling lists of Nobel laureates in the early twentieth century - Sneis, Jørgen; Spoerhase, Carlos (Orbis litterarum, 2023)
This paper analyzes what may be called Olympic Internationalism as a framework for comparing literatures in the early twentieth century. Specifically, it analyzes the practice of tabulating information about the Nobel Prize—in the Swedish Academy, the international press, and repositories of general knowledge such as encyclopedias—and argues that the international circulation of such “thin knowledge” (Orsini) formed the very basis for that framework of comparison. This, it is further argued, played a crucial role in shaping the international perception of what world literature is and in making the Nobel Prize in Literature what it is: a globally acknowledged “world prize.”